The Use of Symbols and Abbreviation Related to KARS Standard Accreditation at Panti Rapih Hospital - Savitri Citra Budi, Vitri (97724D7172DDD, 2014)
Background: Standarization of the suitability of symbol and abbreviation used on medical record’s document as one of KARS accreditation assessment component on Information and Communication Management chapter. Based on early study, Panti Rapih Hospital which prepared KARS accreditation and already have book about its guideliness which already accepted by hospital director. Purpose: Knowing the suitability percentage of symbols and abbreviations on medical record file; Knowing the factors of use of medical symbols and abbreviations. Metodology : Using descriptive kind of research with case study approachment. Data gathering methods are observation, interview and study document. Data validation using triangulation methods. Result: [1] Suitability percentage of symbol usage on patient’s medical records document are gaining amount 100% at four superior considered specialist. [2] Suitability percentage of abbreviation usage are gaining 75,11% for surgical specialist, 79,42% for obstetric and gynecology specialist, 84,63% for pediatrics specialist, 84,98% for internist specialist. [3] The barrier factor from Man are the lack of awareness and carelessness of health practitoner and nursery about the usage of medical symbol and abbreviation, founding difficulty to verificate, there was abbreviation which use withoutthe legalization from hospital directors, from the method is the lackness of socialization related to its usage.